Violence and the importance of networking in service provision (Brazilian Journal of Health Research, 2025)
Individuals experiencing violence must be seen in their individuality and subjectivity. Professionals working with this group must recognize both victims — direct or indirect — and perpetrators of violence as subjects of rights. This understanding requires humanized care and demands a networked approach, given the complexity of the harm and its impacts on health and the social sphere. Assistance to victims of violence still faces challenges due to the invisibility of the phenomenon, lack of knowledge about established care flows, and the fragility of structured care networks. Integrated action among health, education, justice, public security, social assistance, and community sectors is essential to promote safe and healthy environments, prevent violence, and ensure the protection of human rights. Building effective, articulated, and cooperative intersectoral networks is fundamental for addressing violence. Investing in the continuous training of professionals, the establishment of care flows, and the strengthening of public policies is indispensable for ensuring comprehensive and humanized care for individuals experiencing violence.
Keywords: Violence; Care networks; Intersectorality; Public health; Human rights